Comunicação organizacional digital e recursos de acessibilidade: influências da pandemia de Covid-19 no facebook do Burger King Brasil - Magalhães, Guilherme Mori [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
One of the reflexes of the Covid-19 pandemic was the intensified virtualization of the relationship between publics and organizations. For some time, it was expected that this would bring about changes in the digital environment, especially regarding the inclusion of people with disabilities. This study verifies how the intensification of digital interaction during the new coronavirus pandemic has influenced the usage of accessible formats for people with sensory disability on Burger King Brazil’s digital communication on Facebook. For this, we carried out an analysis of web accessibility and a survey of the offer of alternative formats of content and communicational accessibility resources. The results point to the reconfiguration of barriers in this new context, motivated by the open nature of organizations.

Um dos reflexos da pandemia de Covid-19 foi o fortalecimento da relação entre públicos e organizações na internet. Por algum tempo, esperou-se que isso acarretaria em mudanças no ambiente digital, principalmente sobre a inclusão de pessoas com deficiência. Este estudo objetiva verificar como a intensificação das formas de interação no ambiente digital durante a pandemia do novo coronavírus influenciou mudanças no uso de formatos acessíveis para pessoas com deficiência sensorial na comunicação digital do Burger King Brasil no Facebook. Para isso, foi feita uma análise de acessibilidade web e um levantamento da oferta de formatos alternativos de conteúdo e recursos de acessibilidade comunicacional. Os resultados apontam para a reconfiguração das barreiras nesse novo contexto, motivada pela natureza aberta das organizações.
Digital organizational communication and accessibility resources: Covid-19 pandemic influence on Burger King Brazil's facebook
Keywords: Organizational communication; Accessibility; Social media; Sensory disability; Participation; Comunicação empresarial; Acessibilidade; Redes sociais on-line; Participação; Comunicação organizacional; Deficiência sensorial